Desert Meteorology. - Warner, Thomas T. (Cambridge University Press, 2004)
Aridity prevails over more than one third of the land area of the Earth and over a significant fraction of the oceans as well. Yet to date there has been no comprehensive reference volume or textbook dealing with the weather processes that define the character of desert areas. Desert Meteorology fills this gap by treating all aspects of desert weather, such as large-scale and local-scale causes of aridity; precipitation characteristics in deserts; dust storms; floods; climate change in deserts; precipitation processes; desertification; land-surface physics of deserts; numerical modelling of de.